Outcomes of an electronic medical record (EMR)–driven intensive care unit (ICU)-antimicrobial stewardship (AMS) ward round: Assessing the "Five Moments of Antimicrobial Prescribing". (13th August 2019) - Devchand, Misha; Stewardson, Andrew J.; Urbancic, Karen F.; Khumra, Sharmila; Mahony, Andrew A.; Walker, Steven; Garrett, Kent; Grayson, M. Lindsay; Trubiano, Jason A.
Abstract: Objective: The primary objective of this study was to examine the impact of an electronic medical record (EMR)–driven intensive care unit (ICU) antimicrobial stewardship (AMS) service on clinician compliance with face-to-face AMS recommendations. AMS recommendations were defined by an internally developed "5 Moments of Antimicrobial Prescribing" metric: (1) escalation, (2) de-escalation, (3) discontinuation, (4) switch, and (5) optimization. The secondary objectives included measuring the impact of this service on (1) antibiotic appropriateness, and (2) use of high-priority target antimicrobials. Methods: A prospective review was undertaken of the implementation and compliance with a new ICU-AMS service that utilized EMR data coupled with face-to-face recommendations. Additional patient data were collected when an AMS recommendation was made. The impact of the ICU-AMS round on antimicrobial appropriateness was evaluated using point-prevalence survey data. Results: For the 202 patients, 412 recommendations were made in accordance with the "5 Moments" metric. The most common recommendation made by the ICU-AMS team was moment 3 (discontinuation), which comprised 173 of 412 recommendations (42.0%), with an acceptance rate of 83.8% (145 of 173). Data collected for point-prevalence surveys showed an increase in prescribing appropriateness from 21 of 45 (46.7%) preintervention (October 2016) to 30 of 39 (76.9%) during the study period (September 2017). Conclusions: The integration of EMR with an ICU-AMS program allowed us to implement a new AMS service, which was associated with high clinician compliance with recommendations and improved antibiotic appropriateness. Our "5 Moments of Antimicrobial Prescribing" metric provides a framework for measuring AMS recommendation compliance.